Placental MRI and its application to fetal intervention. (28th July 2019) - Aughwane, Rosalind; Ingram, Emma; Johnstone, Edward D.; Salomon, Laurent J.; David, Anna L.; Melbourne, Andrew
Abstract: Objective: Magnetic resonance imaging (MRI) of placental invasion has been part of clinical practice for many years. The possibility of being better able to assess placental vascularization and function using MRI has multiple potential applications. This review summarises up‐to‐date research on placental function using different MRI modalities. Method: We discuss how combinations of these MRI techniques have much to contribute to fetal conditions amenable for therapy such as singletons at high risk for fetal growth restriction (FGR) and monochorionic twin pregnancies for planning surgery and counselling for selective growth restriction and transfusion conditions. Results: The whole placenta can easily be visualized on MRI, with a clear boundary against the amniotic fluid, and a less clear placental‐uterine boundary. Contrasts such as diffusion weighted imaging, relaxometry, blood oxygenation level dependent MRI and flow and metabolite measurement by dynamic contrast enhanced MRI, arterial spin labeling, or spectroscopic techniques are contributing to our wider understanding of placental function. Conclusion: The future of placental MRI is exciting, with the increasing availability of multiple contrasts and new models that will boost the capability of MRI to measure oxygen saturation and placental exchange, enabling examination of placental function in complicated pregnancies. Abstract : What is already known about this topic? Placental function is responsible for significant morbidity and mortality in fetal growth restriction and in monochorionic twin pregnancies complicated by selective growth restriction and transfusion conditions. Our ability to diagnose placental dysfunction in utero is currently limited, with implications for clinical decision making. MRI is capable of imaging the whole human placenta at any gestational age and has been shown to demonstrate differences between normally functioning placentas and those with growth restriction. What does this study add? This review summarises up‐to‐date research on placental function that has been carried out using different MRI modalities. We discuss how combinations of these techniques have much to contribute to fetal conditions amenable for therapy such as singletons at high risk for FGR through early recognition, appropriate management, and monitoring response to treatment and monochorionic twin pregnancies for planning surgery and counselling for selective growth restriction and transfusion conditions.